WAYS TO FORM A MIDDLE CLASS OF OWNERS - Tashmukhamedova Makhina Kudratbek Qizi (Scholar Express Journals, 2024)
In this article has been researched the social and economic significance of the formation of the middle class of owners and the factors that affect them.
Keywords: Property owner; denationalization; nongovernmental sector